Dental Implants in Pediatric Dentistry: A Literature Review. - Soares Fernandes, Ana Paula; Battistella, Márcio Antônio (Brazilian Journal of Implantology and Health Sciences, 2020)
The use of osseointegrated implants has been increasingly widespread in the adult population, however in children there is a certain lack in the literature on the application of this technique. The bone growth and development factor must be well analyzed, and the pediatric dentist must be able to suggest the use of this treatment option for oral rehabilitation, when necessary. This article discusses bone growth and development of the craniofacial region, presents relevant aspects of the literature and discusses the use of this technique in pediatric patients.